The factors that influence customer loyalty towards Telecommunication Company (Telco) in Kota Bharu, Kelantan / Nur Aisah Samsudin - Samsudin, Nur Aisah (Bachelor of Business Administration (Hons) Marketing, 2015)
The aim of this study was to examine the factors that influence customer loyalty towards Telecommunication Company (Telco) in Kota Bharu, Kelantan. There are five (5) independent variable that been studied, which were network coverage, price, promotion, customer service and customer satisfaction. Moreover, questionnaires had been used in order to get feedback from consumers. Researcher had distributed 100 questionnaires to consumers around Kota Bharu. The researcher use probability sampling. The method that been used are simple random technique. The data collected was then tested on its frequency and reliability analysis, regression analysis, Pearson correlation analysis were used to test the hypothesis in this study. The finding on reliability was excellent and it considers that all independent are acceptable. The findings of this paper suggest two factors are significant factors for explaining customer loyalty. Based from the results obtained in this study, researcher suggest some recommendations to make sure both parties which is Telecommunication Company and consumers can fulfill their wants and goals